ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PANGSA SEKTOR PERTANIAN, TERHADAP PENURUNAN ANGKA KEMISKINAN DI KABUPATEN/KOTA PROVINSI NUSA TENGGARA BARAT TAHUN 2009-2014 - Sri Atma Hartini (Valid: Jurnal Ilmiah, 2016)
This study aims to analyze the influence of economic growth, the share of the agricultural sector, the poverty rate in the District / City of West Nusa Tenggara province in 2009-2014. The research data is collected using data collection and case study data collection technique used was documentation. While analysis tools used in this study is a panel data regression (poled data), using 10 data crossection and the 6-year time series data from 2009 to 2014. The results of this study indicate that economic growth, the share of the agricultural sector that the variables used in the study was able to explain the variation in the change of poverty rate of 82.83% while 17.17% is explained by or influenced by other factors outside the study From the test results simultaneously, economic growth and the share of the agricultural sector has a significant influence on the level of poverty in the District / City of West Nusa Tenggara province in 2009-2014. The test results are only a partial share of the agricultural sector, which has a significant effect in reducing poverty in the District / City of West Nusa Tenggara Province. Based on the analysis of the government in the District / City of West Nusa Tenggara province should enhance the role of the agricultural sector through increased investment in the agricultural sector so that an increase of the share of the agricultural sector in order to reduce the level of poverty in the District / City of West Nusa Tenggara Province